Risankizumab-Aggravated Crusted Scabies in a Patient with Down Syndrome - Yseult Senterre; Gaëlle Jouret; Patrick Collins; Arjen F. Nikkels (Adis, Springer Healthcare, 2020)
Abstract Risankizumab, an interleukin (IL)-23 antagonist, is a highly effective treatment for moderate to severe psoriasis. Crusted scabies (CS) is a rare and severe form of scabies, occurring mainly in immunosuppressed patients and/or neurologically or mentally ill patients. A young girl with Down syndrome was diagnosed with a hyperkeratotic form of psoriasis. As treatment with topical dermocorticosteroids, UVB-phototherapy and acitretin for 6 weeks did not improve the lesions, two injections of risankizumab were administered. Following these injections, the lesions became rapidly even more severely crusted, and new lesions appeared on the extremities and the face of the patient. There was histological evidence of a high charge of scabies, leading to a diagnosis of CS. The patient was hospitalized and successfully treated by local permethrine and systemic ivermectine. This case suggests that even though anti-IL23 antagonists display an excellent overall safety profile, a particular caution for infections should still be respected in patients with underlying risk factors.